Social and Stylistic Stratification in the Speech Prosody of the Spanish of Mérida, Yucatán - Mendoza, Érika (2023)
The aim of this paper is to present the social and stylistic variation in the speech prosody of the Spanish of Mérida, Yucatán. Assertive utter-ances from sociolinguistic interviews and discourse completion tasks are analyzed considering the social variables of age, gender and educational level. The prosodic analysis is carried out within the Autosegmental Metrical model (Pierrehumbert 1980, Ladd 2008) and with the Sp_ToBI labeling conventions (Hualde & Prieto 2015). The results show that this variety of Spanish is characterized by a prominent descent starting from the first tonal peak, the early-peak alignment in some prenuclear posi-tions, and the presence of some non-falling boundary tones. The social and stylistic variation suggests that the last two are features that indicate vernacularity.